Digitalization of Language, Literature, Regional Culture and its Learning as a Transformation of the Society 5.0 Era - Nurjanah, Nunuy; Sutisna, Ade (Jayapangus Press, 2025)
The existence of regional languages continues to experience a decline in the number of speakers in the world, especially in Indonesia. In order to stop this situation, it is necessary to have prevention efforts. One of these efforts is digitization as a form of transformation in the era of society 5.0. This digitization effort is an act of transforming the form or transfer of print, audio and video media into digital form. This paper aims to describe certain media that can be used as innovations in language-based digital learning, especially Sundanese. The media are in the form of digital learning applications (MABS: Sundanese Teaching Materials).